On Church Governance of Northern Orthodox Parishes in Pskov Region during the German occupation and within the “New Course” - Konstantin Obozny (Вестник Свято-Филаретовского института, 2016)
This article strives to make a comparison study on principles and practical peculiarities of church governance within Pskov diocese during the German occupation and in the early post-war years. This period is characterised by such common features as the absence of ruling bishop, the incoordinate diocesan administration, the numerical lack of parish clergy, the high activism of church laity, and the interference of secular authorities in internal church issues. The German occupation authorities meddled in church issues from pragmatic considerations of their military campaign with USSR. The Soviet government influenced busily the diocese’s church life following the objectives of the conceptual Orthodox change in Soviet Russia.